2008
DOI: 10.1902/jop.2008.070289
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasound on Bone Dimensional Changes Following Extraction: A Pilot Study

Abstract: In this pilot study, there was no significant benefit to ultrasound in absolute bony dimensional changes following tooth extraction. There was a significant interaction between the treatment rendered (ultrasound versus control) and the change in buccal ridge height relative to baseline ridge width at the crest and 3 mm apical to the crest. This benefit was apparent in wide sockets compared to narrow sockets; however, the clinical importance of these relative dimensional changes in the ultrasound group are diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
(57 reference statements)
3
29
0
7
Order By: Relevance
“…It was applied twice a week for 20 minutes each session that commenced two weeks after stage I implant surgery and continued for 10 weeks. The intensity of ultrasound therapy used was 30 mW/cm2 with a frequency of 1.5 MHz and temporal average power of 20 mW, as per Kerr et al 15) . The same ultrasound therapy protocol was repeated 2 weeks after crown installation and continued for another 10 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was applied twice a week for 20 minutes each session that commenced two weeks after stage I implant surgery and continued for 10 weeks. The intensity of ultrasound therapy used was 30 mW/cm2 with a frequency of 1.5 MHz and temporal average power of 20 mW, as per Kerr et al 15) . The same ultrasound therapy protocol was repeated 2 weeks after crown installation and continued for another 10 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The coronal and sagittal reference lines were set at the intersection point at the implant center that was to be examined. The peri-impant bone dimension measurements were done per Uzbek et al 15) . For linear measurements of bone height and width around dental implants, bony landmarks (points) were located and identifi ed and Linear Distance-Line connecting between two points were measured.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the height and especially the width of the alveolar ridge decrease significantly after tooth extraction (Lam, 1960;Pietrokovski and Massler, 1967;Johnson, 1969;Jahangiri et al, 1998;Schropp et al, 2003;Araujo and Lindhe, 2005;Kerr et al, 2008;van der Weijden et al, 2009). A clinical study reported a reduction of 50% in the width of the alveolar ridge at 12 months and an average bone loss of between 5 and 7 mm (Schropp et al, 2003), leading to insufficient bone volume at the implant site.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, concurrent with new bone growth into the extraction socket, there is also well-documented resorption of the alveolar ridge, resulting in its decreased height and width (Lam, 1960;Pietrokovski and Massler, 1967;Johnson, 1969;Jahangiri et al, 1998;Schropp et al, 2003;Araujo and Lindhe, 2005;Kerr et al, 2008;van der Weijden et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, concurrent with new bone growth into the extraction socket, there is also resorption of the alveolar bone. Many studies have demonstrated that the height and especially the width of the alveolar bone decrease significantly after tooth extraction (Lam, 1960;Pietrokovski and Massler, 1967;Johnson, 1969;Jahangiri et al, 1998;Schropp et al, 2003;Araujo and Lindhe, 2005;Kerr et al, 2008;van der Weijden et al, 2009), leading to insufficient bone volume at the implant site.…”
Section: Introductionmentioning
confidence: 99%